Gas concentration detection via multi-channeled air sampling method. Issue 2 (20th March 2017) - Hou, Longfei; Wang, Dan; Du, Bingxuan; Qian, Xinmin; Yuan, Mengqi
Abstract : Purpose: The purpose of this paper is to present a new technique for monitoring gas leakage in underground pipelines to prevent dangerous explosions. Design/methodology/approach: A novel system for monitoring methane concentration in underground spaces was developed by integrating the multi-channeled air sampling method with an infrared gas sensor. A pipe installation methodology (without excavation) was established and verified accordingly. Findings: The proposed approach was proven successful in reducing the quantity of sensors needed for real-time monitoring of underground pipeline leakage by about 80 per cent. Furthermore, this system lowers total operational cost by as much as 60 per cent. Originality/value: The results presented here represent a possible solution to reducing the public safety risks associated with explosions and fires caused by pipeline leakage in underground spaces. Its total cost is low and its monitoring efficiency is high.